OX40 ligand and OX40 are increased in atopic dermatitis lesions but do not correlate with clinical severity. (31st May 2012) - Ilves, T.; Harvima, I.T.
Abstract: Background  The interaction between the OX40 ligand (OX40L) and OX40 has been suggested to have pathogenetic significance in atopic dermatitis (AD). Objective  The purpose of this study was to investigate the expression and relevance of OX40L and OX40 in AD skin. Methods  OX40L and OX40 were stained immunohistochemically on the cryosections of the lesional and non‐lesional skin of 17 subjects with moderate‐to‐severe AD and of 10 patients with psoriasis vulgaris. Phorbol myristate acetate (PMA) stimulated keratinocytes and cell membrane preparations from PMA‐stimulated keratinocytes or LAD‐2 mast cells were incubated with peripheral blood mononuclear cells (PBMC) in the presence or absence of blocking monoclonal antibodies to OX40L, CD30L or ICAM‐1. Results  We show for the first time that the staining intensity of OX40L and the number of OX40 + cells are significantly greater in the lesional dermis than in the healthy‐looking dermis in AD ( P  <   0.001 in both comparisons) and also in psoriasis ( P  =   0.01 and P  <   0.001 respectively), but neither molecule correlate significantly with the clinical severity of AD. Living keratinocytes and cell membranes from LAD‐2 mast cells and keratinocytes increased the PBMC proliferation response. Anti‐OX40L antibody inhibited, in a similar fashion as anti‐ICAM‐1 and anti‐CD30L, PBMC proliferation induced by LAD‐2 membranes, but stimulated that induced by keratinocytes. Conclusion  Our findings provide evidence for the involvement of OX40 and OX40L in the pathogenesis of AD though they are not specific to AD and in vitro results suggest complex interaction.